2015
DOI: 10.1007/s00125-015-3714-5
|View full text |Cite|
|
Sign up to set email alerts
|

Physical activity attenuates the mid-adolescent peak in insulin resistance but by late adolescence the effect is lost: a longitudinal study with annual measures from 9–16 years (EarlyBird 66)

Abstract: Aims/hypothesis The aim of this work was to test whether the mid-adolescent peak in insulin resistance (IR) and trends in other metabolic markers are influenced by long-term exposure to physical activity. Methods Physical activity (7 day ActiGraph accelerometry), HOMA-IR and other metabolic markers (glucose, fasting insulin, HbA 1c , lipids and BP) were measured annually from age 9 years to 16 years in 300 children (151 boys) from the EarlyBird study in Plymouth, UK. The activity level of each child was charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 37 publications
2
23
1
Order By: Relevance
“…We have previously shown that physical activity attenuates the mid‐adolescent peak in IR and that this effect disappears by 16 years, independent of adiposity and pubertal stage . In our final model, however, physical activity explained only a small proportion of the gender difference in IR.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…We have previously shown that physical activity attenuates the mid‐adolescent peak in IR and that this effect disappears by 16 years, independent of adiposity and pubertal stage . In our final model, however, physical activity explained only a small proportion of the gender difference in IR.…”
Section: Discussionmentioning
confidence: 62%
“…Children's MVPA varied little from 9 to 16 years, and in order to characterize the overall long‐term physical activity level of each child, their MVPA was averaged across all 8 time points. In doing so, the children were ranked according to their activity levels throughout the whole period with 95% reliability, compared with 70% reliability when using 1 annual measure of physical activity …”
Section: Methodsmentioning
confidence: 99%
“…In a follow‐up from ages 9 to 16, children in the more active groups (boys: ≥50 min MVPA per day, girls: ≥35 min MVPA per day) attenuated the mid‐adolescent peak in HOMA‐IR compared with the less active group, independent of body fat percentage and pubertal status . However, at age 16, there were no differences between the activity groups . Similarly, an Estonian study ( n = 120) found no association between MVPA and HOMA‐IR in boys .…”
Section: Resultsmentioning
confidence: 92%
“…The EarlyBird cohort found that number of minutes spent ≥3 METs were associated with lower mean arterial BP in boys from ages 5 to 8 . From the same cohort, diastolic BP (DBP) were marginally lower in active boys (≥50 min MVPA per day) when compared with those that were less active throughout adolescence (ages 9 to 16) . Similarly, one study observed a favourable but non‐significant effect on SBP in the intervention group between baseline and post‐intervention .…”
Section: Resultsmentioning
confidence: 98%
“…However, despite of insulin resistance increases with age, racial health disparities and pubertal status (Ball et al, 2006), some authors have shown in girls and boys from 9 to 16 years an interesting relationship between physical activity and decreases in both insulin and the homeostasis model assessment of insulin resistance (HOMA-IR) marker changes throughout development (Metcalf et al, 2015). …”
Section: Introductionmentioning
confidence: 99%